Whole-body microbiota of newborn calves and their response to prenatal vitamin and mineral supplementation - Luecke, Sarah M.; Holman, Devin B.; Schmidt, Kaycie N.; Gzyl, Katherine E.; Hurlbert, Jennifer L.; Menezes, Ana Clara B.; Bochantin, Kerri A.; Kirsch, James D.; Baumgaertner, Friederike; Sedivec, Kevin K.; Swanson, Kendall C.; Dahlen, Carl R.; et al. (Frontiers in Microbiology, 2023)
Early life microbial colonization and factors affecting colonization patterns are gaining interest due to recent developments suggesting that early life microbiome may play a role in Developmental Origins of Health and Disease. In cattle, limited information exists on the early microbial colonization of anatomical sites involved in bovine health beyond the gastrointestinal tract. Here, we investigated 1) the initial microbial colonization of seven different anatomical locations in newborn calves, and 2) whether these early life microbial communities and 3) serum cytokine profiles are influenced by prenatal vitamin and mineral (VTM) supplementation. Samples were collected from the hoof, liver, lung, nasal cavity, eye, rumen (tissue and fluid), and vagina of beef calves that were born from dams that either received or did not receive VTM supplementation throughout gestation (n=7/group). Calves were separated from dams immediately after birth and fed commercial colostrum and milk replacer until euthanasia at 30 h post-initial colostrum feeding. The microbiota of all samples was assessed using 16S rRNA gene sequencing and qPCR. Calf serum was subjected to multiplex quantification of 15 bovine cytokines and chemokines. Our results indicated that the hoof, eye, liver, lung, nasal cavity, and vagina of newborn calves were colonized by site-specific microbiota, whose community structure differed from the ruminal-associated communities (0.64≥R2≥0.12, P≤0.003). The ruminal fluid microbial community was the only one that differed by treatment (P<0.01). However, differences (P<0.05) by treatment were detected in microbial richness (vagina); diversity (ruminal tissue, fluid, and eye); composition at the phylum and genus level (ruminal tissue, fluid, and vagina); and in total bacterial abundance (eye and vagina). From serum cytokines evaluated, concentration of chemokine IP-10 was greater (P=0.02) in VTM calves compared to control calves. Overall, our results suggest that upon birth, the whole-body of newborn calves are colonized by relatively rich, diverse, and site-specific bacterial communities. Noticeable differences were observed in ruminal, vaginal, and ocular microbiota of newborn calves in response to prenatal VTM supplementation. These findings can derive future hypotheses regarding the initial microbial colonization of different body sites, and on maternal micronutrient consumption as a factor that may influence early life microbial colonization.